EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) DAN NUMBERED HEADS TOGETHER (NHT) DITINJAU DARI KECERDASAN MAJEMUK PESERTA DIDIK - Widyawati, Santi; Mardiyana, Mardiyana; Iswahyudi, Gatut (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2014)
Abstract: The objectives of this research were to investigate: (1) which learning model of the TSTS model, the NHT model, and the direct learning model resulted in a better learning achievement in mathematics; (2) which students of the students with mathematical-logical, interpersonal, and linguistic intelligence had a better learning achievement in mathematics; (3) in each category of the multiple intelligences, which learning model of the TSTS model, the NHT model, and the direct learning model resulted in a better learning achievement in mathematics; and (4) in each learning model, which students of the students with mathematical-logical, interpersonal and linguistic intelligence had a better learning achievement in mathematics. This research used the quasi experimental research method with the factorial design of 3 x 3. Its population was all of the students in Grade VII of Junior Secondary Schools of Metro City. The size of the samples was 269 students. They were taken by using the stratified cluster random sampling technique. The instruments to gather the data of the research were test of learning achievement in mathematics and questionnaire of multiple intelligences. The proposed hypotheses of the research were tested by using the two-way analysis of variance with unbalanced cells. The results of the research were as follows. 1) The TSTS model resulted in a better learning achievement than the NHT model and direct model, and the NHT model resulted in a better learning achievement than the direct learning model. 2) The students with mathematical-logical intelligence had a better learning achievement than those with interpersonal and linguistic intelligences, and the students with interpersonal intelligence had a better learning achievement than those with linguistic intelligence. 3) In the students with mathematical-logical intelligence, the TSTS model resulted in a better learning achievement than the cooperative learning model of the NHT model, the TSTS model and the NHT model resulted in the same learning achievement as the direct learning model. In the students with interpersonal intelligence, the TSTS model resulted in the same learning achievement as the NHT and direct learning models, and the NHT model resulted in a better learning achievement than the direct learning model. In the students with linguistic intelligence, the TSTS and the NHT model sresulted in the same learning achievement as the direct learning model. 4) In the TSTS model, the students with mathematical-logical intelligence had the same learning achievement as those with interpersonal intelligence but had a better learning achievement than those with linguistic, and interpersonal intelligence had the same learning achievement those with linguistic intelligence. In the NHT model, the students with mathematical-logical, interpersonal, and linguistic intelligences had the same learning achievement. In the direct learning model, the students with mathematical-logical intelligence had a better learning achievement than those with interpersonal and linguistic intelligences, and the students with interpersonal intelligence had the same learning achievement as those with linguistic intelligence. Keywords: TSTS, NHT, multiple intelligences.